Robotic Platform for Automated Search and Rescue Missions of Humans. (4th February 2013) - Kolberg, Eli; Beiderman, Yevgeny; Talyosef, Roy; Amsalem, Raphi; Garcia, Javier; Zalevsky, Zeev
We present a novel type of model incorporating a special remote life signals sensing optical system on top of a controllable robotic platform. The remote sensing system consists of a laser and a camera. By properly adapting our optics and by applying a proper image processing algorithm we can sense within the field of view, illuminated by the laser and imaged by the camera, the heartbeats and the blood pulse pressure of subjects (even several simultaneously). The task is to use the developed robotic system for search and rescue mission such as saving survivals from a fire.